The Mechanization of Nature: Matter, Body, and Motion in Blasius of Parma's Physics - Lagerlund, Henrik, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025, 2025)
This book presents a groundbreaking study of the Italian philosopher and scientist, Blasius of Parma (1350-1416). For the first time in English, it presents key elements of his commentary on Aristotle's Physics both through interpretive analysis and edited texts. The main interpretive claim is that Blasius is an early mechanical philosopher. It shows this by studying six carefully selected aspects of his physics. These six aspects are Blasius' (1) use of mechanics (science of weights), (2) analysis of causality, (3) account of motion, (4) analysis of rarefaction and condensation, (5) view of artifacts, and (6) the use of a new analytical language in physics. Authors of the interpretive essays are Erik Åkerlund, Joël Biard, Henrik Lagerlund, and Sylvain Roudaut.